A Comprehensive State Monitoring System for Lime Shaft Kilns Based on Fuzzy Logic and Improved GMDH Algorithm - Jong Nam Kim; Hong Yon Han; Chun Bae Ma; Yong So; Ryong Hyok Ri; Chung Hyon Hwang (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Efficient and environmentally friendly operation of lime shaft kilns requires accurate real-time monitoring of calcination zone status and flue gas composition. This paper concerns on an integrated monitoring system that combines fuzzy logic and an improved Group Method of Data Handling (GMDH) algorithm. First, 18-rule-based fuzzy logic diagnostic model identifies the operational state of the calcination zone with 94.2% accuracy. Second, an enhanced GMDH algorithm with novel data preprocessing and feature selection mechanisms serves as a soft sensor for predicting CO₂, CO, and O₂ concentrations. Experimental results from a 10,000-ton/year vertical lime kiln demonstrate that the improved GMDH achieves mean absolute errors of 1.5% for CO₂, 2.9% for CO, and 3.0% for O₂, representing a 43.2% improvement over conventional methods. Field application shows 8.3% reduction in fuel consumption and 15.2% reduction in CO emissions, confirming the system's practical value for industrial process optimization. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).